KOMPETENSI MORAL AGAMA ANAK USIA DINI BERDASARKAN TEORI KECERDASAN RUHANIAH - Mar’ati, Rela (TARBAWI:Journal on Islamic Education, 2023)
One of the children's fitrah is moral and religious potential. Religious morals are basic attitudes that must be developed in children in order for children to grow into good and righteous individuals. Therefore, the right formulation is needed so that the child's potential can develop optimally. Research on early childhood development methods has been widely carried out, but there is still little research on the development of early childhood competencies. This study aims to find the moral competence of early childhood religion based on the theory of ruhaniah intelligence. The intelligence of ruhaniah was chosen because it is a divine potential that every child fitrah has from birth. This research uses the library research method, which is to collect library data in the form of reading, recording, and processing libraries without taking data in the field. The results of the research are in the form of developing moral competence of early childhood religion based on the theory of ruhaniah intelligence, namely the aspect of having good-oriented ideals and the aspect of having akhlakul karimah. The aspects of knowing God and believing in God's creation are separated because they have different behavioral indicators. Other aspects are the same as formulated in the early childhood learning reference menu of the PAUD Directoryate. This competence can be a reference for the moral development of early childhood religion for parents or educators.